Effect of preoperative physical education on postoperative outcome in patients with total hip replacement – a prospective cohort study - Ivana Grle; Maki Grle; Damir Franjić; Mateo Bevanda; Mladenka Naletilić (Acta Clinica Croatica)
Hip osteoarthritis is the leading cause of hip pain around the world. Patients are aiming to relieve pain as fast as possible and return to everyday activities. Th e aim of the study was to investigate the effect of preoperative physical education on postoperative rehabilitation in patients after total hip arthroplasty (THA). Th ere were 60 patients divided in two equal groups. One group underwent 3-day preoperative education and the other did not. Th e two groups were compared according to their preoperative and postoperative visual analog scale (VAS), range of motion (ROM), Harris Hip Score (HHS), Western Ontario and McMaster Universities Arthritis Index (WOMAC), and 36-Item Short Form Survey (SF-36). Patient general characteristics were similar in the two groups. Patients that received preoperative training had lower VAS scores, greater ROM, higher HHS and lower WOMAC score on postoperative day 42 (p<0.05 all). Th ese patients had no complications. Th ere were no between-group diff erences in the SF-36 questionnaire. In conclusion, patients that underwent preoperative rehabilitation protocol before THA had lower pain and disability scores and better functional outcomes.